Network Pharmacological Analysis of Hydroxychloroquine Intervention in the Treatment of Iga Nephropathy - Zou, Mengxiao; Xu, Gang; Ge, Shuwang; Guo, Kanglin; Duo, Qian; Cheng, Yichun (Current Pharmaceutical Design, 2025)
BackgroundIgA nephropathy (IgAN) is the most prevalent primary glomerulonephritis globally and has a high propensity to develop into end-stage renal disease (ESRD). Hydroxychloroquine has been proven to reduce proteinuria in IgAN patients, but the precise mechanism remains unclear. Therefore, network pharmacology was used to investigate the mechanism.MethodsPubChem and SwissADME databases were utilized to acquire the structure of hydroxychloroquine. The SwissTargetPrediction, PharmMapper, DrugBank, TargetNet, and BATMAN-TCM databases were then utilized to obtain the targets. The target genes related to IgAN were then gathered from the databases, which included GeneCards, PHARMGKB, DrugBank, OMIM, and DisGeNET. Common targets were obtained by UniProt. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to define the main molecular mechanisms and pathways. Furthermore, a protein-protein interaction (PPI) network was constructed using the STRING tool, and the core targets were obtained by Cytoscape. Finally, molecular docking between the core targets and hydroxychloroquine was performed.Results167 common target genes were acquired by overlapping. The core targets were TNF, ALB, IL1B, JUN, FOS, SRC, and MMP9. The GO and KEGG results showed the targets to be related to the production of inflammatory cytokines and chemokines and were engaged in the toll-like receptor (TLR) signaling pathway. At the same time, the molecular docking results showed that the core targets all combined with hydroxychloroquine closely.ConclusionThis study proved that hydroxychloroquine may treat IgAN through the TLR signaling pathway, and the restraint of TNF, TLR, IL1B, and JUN may be essential for the treatment.
Keywords: Hydroxychloroquine